Efficient adsorptive removal of Congo Red dye using activated carbon derived from Spathodea campanulata flowers - Sujesh Sudarsan; Gokulakrishnan Murugesan; Thivaharan Varadavenkatesan; Ramesh Vinayagam; Raja Selvaraj (Scientific Reports)
Abstract This report investigates the preparation, characterization, and application of activated carbon derived from Spathodea campanulata flowers (SCAC) to remove Congo Red (CR) dye from aqueous streams. SCAC was synthesized using orthophosphoric acid activation which yielded a mesoporous material with a specific surface area of (986.41 m2/g), significantly exceeding values reported for flower-derived activated carbons in the available literature. Field emission scanning electron microscopy (FESEM) image revealed an irregular, rough surface morphology pre-adsorption, which became smoother post-adsorption, indicating successful CR attachment. Elemental analysis through energy-dispersive x-ray spectroscopy (EDS) and X-ray photoelectron spectroscopy (XPS) confirmed an increase in carbon content and the appearance of sulfur, verifying CR uptake. Adsorption kinetics obeyed the pseudo-second-order equation, signifying chemisorption, while the equilibrium dataset fitted better to the Langmuir model, with R2 of 0.9944, suggesting a monolayer adsorption mechanism with a maximum adsorption capacity of 59.27 mg/g. Thermodynamic analysis revealed spontaneous and endothermic adsorption process. Desorption studies showed methanol as the most effective desorbing agent, with SCAC retaining considerable adsorption capacity across six cycles, highlighting its reusability. In tests with real water matrices, SCAC demonstrated significantly higher removal efficiency in natural waters than control, suggesting enhanced adsorption in complex matrices. These findings underscore the practical applicability of SCAC in real-world wastewater treatment, offering a promising solution for large-scale industrial applications.